Reclaimed adab in the social sphere of 21st century modern muslims - Annuar, Hairul Azlan; Che Abdul Hamid, Khamsi (Sejahtera Consumerism Kulliyyah of Economics and Management Sciences IIUM, 2025)
A seeker of knowledge in Islam is to become a good man. The concept of ‘good man’ extends beyond the general social interpretation; it begins fundamentally with the individual self. A man who is unjust to his own self cannot be expected to act justly towards others. Unjust in the sense of pursuing one's own self-interest above God’s Will and interest, indicating a failure to put reality in its proper place. The worldview in Islam inculcates the awareness that man is a humble slave before God (‘abd) and surrenders his will to God’s Will before he qualifies to be His vicegerent (Khalifah) on earth. With these qualifications and awareness that he is indebted to his existence in this world, granted upon him by God, man can uphold the Shari’ah rules, as revealed through the words of the Holy Prophet Muhammad (may God bless and give him peace) and his noble companions and followers (blessing and peace be upon them all). These paths preserve the original nature of Islam throughout generations (AlAttas, 2020). These concepts lay the foundation for believers to act with adab and akhlak in fulfilling their duties and responsibilities, enabling them to become Muslims who restore justice and prevent oppression across generations within the Ummah, despite cultural differences, thereby advancing the modern world.